2022
DOI: 10.3390/microorganisms10112275
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-Spike Antibody and T-Cell Responses Elicited by a Homologous Third mRNA COVID-19 Dose in Hemodialysis and Kidney Transplant Recipients

Abstract: The effect of a third vaccine dose (3D) of homologous mRNA vaccine on blood levels of SARS-CoV-2-receptor binding domain (RBD)-total antibodies was assessed in 40 hemodialysis patients (HD) and 21 kidney transplant recipients (KTR) at a median of 46 days after 3D. Anti-RBD antibodies were detected in 39/40 HD and 19/21 KTR. Overall, 3D boosted anti-RBD antibody levels (median: 58-fold increase). Neutralizing antibodies (NtAb) against the Wuhan-Hu-1, Delta, and Omicron variants were detected in 14, 13, and 11 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…As in AIMs assay, the magnitude of IFN-γ production detected against Omicron was lower in both groups. While the vast majority of the scientific studies aimed at measuring the cellular immune response elicited by vaccination were based on ELISA or ELISPOT instead that on activation markers, the results obtained were congruent with our observations [ 22 , 44 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As in AIMs assay, the magnitude of IFN-γ production detected against Omicron was lower in both groups. While the vast majority of the scientific studies aimed at measuring the cellular immune response elicited by vaccination were based on ELISA or ELISPOT instead that on activation markers, the results obtained were congruent with our observations [ 22 , 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…The booster shot induced production of nAbs against the ancestral SARS-CoV-2 strain also in primary non-responder KTR subjects [ 13 , 14 , 15 ], although some of the recipients did not mount a detectable humoral immune response following the 3rd dose [ 16 ], while nAb titers were lower against Alpha, Beta, Delta and Omicron variants in both KTR and the general population [ 17 , 18 ], as confirmed by pseudotyped lentivirus [ 19 ] and live virus-based tests [ 20 ]. Moreover, the role of T cells in conferring protection has been underlined [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, their ability to neutralize Omicron is lower than that of SARS-CoV-2 or other variants. Similarly, Panizo et al ( 109 ) examined the impact of a third dose of a matching mRNA vaccine on SARS-CoV-2 RBD total antibody levels in a cohort of 21 KTRs. They detected RBD-specific antibodies in 19 of the 21 KTRs and identified neutralizing antibodies against the SARS-CoV-2, Delta, and Omicron variants, indicating the effectiveness of the third dose.…”
Section: Vaccination For Prevention Of Omicron Infection In Ktrsmentioning
confidence: 99%
“…Meanwhile, CD4 + helper T cells provide signals that support the development of antibody responses and other functions [ 3 ]. However, the immune response is suboptimal in patients with chronic diseases (such as hypertension and cardiovascular disease) and those receiving immunosuppressive therapy, such as kidney transplant patients or patients requiring dialysis [ 4 , 5 , 6 ]. Anti-SARS-CoV-2 vaccine data showed that seroconversion rates remained reduced in immunocompromised groups (organ transplant recipients, patients with solid or hematological cancers, or patients with immune-mediated inflammatory disorders) compared with immunocompetent controls [ 7 ].…”
Section: Introductionmentioning
confidence: 99%